Rational Design of LaNiO3/Carbon Composites as Outstanding Platinum‐Free Photocathodes in Dye‐Sensitized Solar Cells With Enhanced Catalysis for the Triiodide Reduction Reaction. Issue 7 (20th June 2017) - Wang, Wei; Liu, Yu; Zhong, Yi Jun; Wang, Lianzhou; Zhou, Wei; Wang, Shaobin; Tadé, Moses O.; Shao, Zongping
Abstract : In many photovoltaics (PVs), including dye‐sensitized solar cells (DSSCs), triiodide/iodide (I3 − /I − ) redox couple plays an important role, and an active and stable electrocatalyst is required for promoting I3 − reduction reaction (IRR) to minimize efficiency losses. Platinum (Pt) is the state‐of‐the‐art electrocatalyst for IRR, which unfortunately suffers from high cost and poor stability. Herein, strongly coupled LaNiO3 perovskite/carbon composites are developed for the first time as highly efficient, stable and low‐cost electrocatalysts for IRR to enable better DSSCs. High‐energy ball milling of crystallized LaNiO3 with carbon material is applied for the facile synthesis of LaNiO3 /carbon composites. This ball‐milling process simultaneously leads to partial reduction of LaNiO3 by carbon with the creation of oxygen vacancies inside the perovskite oxide lattice, a decrease in LaNiO3 particle size and the creation of strong coupling between LaNiO3 and carbon. Particularly, DSSC with LaNiO3 /multi‐walled carbon nanotubes photocathode delivers a high power conversion efficiency of 9.81% with an attractive enhancement of 21% compared with Pt electrocatalyst, superior to most state‐of‐the‐art highly efficient Pt‐free photocathodes in DSSCs. LaNiO3 or carbon alone demonstrates a much poorer performance. Moreover, LaNiO3 /carbon composites demonstrate excellent operational stability. This study highlights the extended applications of perovskites in other I3 − /I − ‐mediated PVs, electrochromic devices or batteries. Abstract : The rational design of LaNiO3 /carbon composites as novel and outstanding Pt‐free photocathodes in dye‐sensitized solar cells (DSSCs) is reported. These strongly coupled LaNiO3 perovskite/carbon composites are developed by a facile mechano‐chemical method, demonstrating a highly attractive power conversion efficiency of 9.81% and an excellent long‐term durability in DSSCs, among the best‐performing Pt‐free photocathodes reported so far.